Phenols and peroxidase activity in Pepper yellow leaf curl Thailand virus (PepYLCThV) resistant and susceptible chili (Capsicum annuum L.) genotypes - Kingkampang, H.; Teerarak, M.; Kramchote, S.; Techawongstien, S.; Suwor, P. (International Journal of Agricultural Technology, 2020)
Chilli (Capsicum annuum L.) is most commonly cultivated species. Pepper yellow leaf curl virus (PepYLCV) causes serious leaf curl disease of chili. In order to understand plant defence mechanism to PepYLCV disease, the study reported a response of total phenols and peroxidase activity in two contrasting pepper genotypes (resistant and susceptible) against PepYLCThV. The total phenolic content of uninoculated plants in susceptible genotype (KKU-P31118) showed higher value than resistance genotype (9853-123) at both stages. However, the amount of total phenolic content in resistant genotypes was increased in juvenile and mature leaves in response to inoculation with PepYLCThV. In case of susceptible one, it was decreased as compared to uninoculated control. On the other hand, the peroxidase activity in chilli genotypes and at different stage of leaves was increased every week after inoculation and increased as a comparison to uninoculated plants. Hence, our finding suggested that the total phenols may act as defence mechanism in resistant genotype 9853-123.